The Impact of the Legal Framework and Reporting Mechanisms in Eradicating Sexual Harassment in the Workplace in Indonesia - Kalijunjung Hasibuan; Muhamad Romdoni (Eastasouth Institute, 2023)
This study looks into how reporting procedures and legal frameworks affect the effort to end sexual harassment in Indonesian workplaces. Even with current laws in place, sexual harassment is still a common occurrence, so a thorough review of the legal system is required. This study identifies important legislative provisions, evaluates their efficacy, and investigates the difficulties faced by victims using a mixed-methods methodology that includes legal analysis, questionnaires, and interviews. The results provide insights from both global and regional viewpoints, point out the advantages and disadvantages of the legislative framework, and clarify the subtleties of reporting procedures. Suggestions for focused changes and enhanced reporting procedures are meant to support Indonesia's continuous endeavors to establish more secure and welcoming work environments.